NIR Photosensitizer for Two-Photon Fluorescent Imaging and Photodynamic Therapy of Tumor - Chen, Lujia; Chen, Meijuan; Zhou, Yuping; Ye, Changsheng; Liu, Ruiyuan (Frontiers in Chemistry, 2021)
Preparation of near-infrared (NIR) emissive fluorophore for imaging-guided PDT (photodynamic therapy) has attracted enormous attention. Hence, NIR photosensitizers of two-photon (TP) fluorescent imaging and photodynamic therapy are highly desirable. In this contribution, a novel D-π-A structured NIR photosensitizer (TTRE) is synthesized. TTRE demonstrates near-infrared (NIR) emission, good biocompatibility, and superior photostability, which can act as TP fluorescent agent for clear visualization of cells and vascular in tissue with deep-tissue penetration. The PDT efficacy of TTRE as photosensitizer is exploited in vitro and in vivo. All these results confirm that TTRE would serve as potential platform for TP fluorescence imaging and imaging-guided photodynamic therapy.